Factoring Quadratic Polynomials Practice Problems
Set 1: Facoring Quadratic Polynomials in Two Steps  Step 1: Determine the Signs
To review factoring quadratic polynomials, go to Factoring Quadratic Polynomials Help
Practice
Determine whether to begin the factoring as ( x + __)( x + __), ( x – __)( x – __), or ( x – __)( x + __).
1. x ^{2} – 5 x – 6 =
2. x ^{2} + 2 x + 1 =
3. x ^{2} + 3 x – 10 =
4. x ^{2} – 6 x + 8 =
5. x ^{2} – 11 x – 12 =
6. x ^{2} – 9 x + 14 =
7. x ^{2} + 7 x + 10 =
8. x ^{2} + 4 x – 21 =
Solutions
1. x ^{2} – 5 x – 6 = ( x –__)( x + __)
2. x ^{2} + 2 x + 1 = ( x + __)( x + __)
3. x ^{2} + 3 x – 10 = ( x – __)( x + __)
4. x ^{2} – 6 x + 8 = ( x – __)( x – __)
5. x ^{2} – 11 x – 12 = ( x – __)( x + __)
6. x ^{2} – 9 x + 14 = ( x – __)( x – __)
7. x ^{2} + 7 x + 10 = ( x + __)( x + __)
8. x ^{2} + 4 x – 21 = ( x – __)( x + __)
Set 2: Factoring Quadratic Polynomials in Two Steps  Step 2: Determine the Constants
To review what factors to check, go to Factoring Quadratic Polynomials Help.
Practice
Factor the quadratic polynomial.
1. x ^{2} – 5 x – 6 =
2. x ^{2} + 2 x + 1 =
3. x ^{2} + 3 x – 10 =
4. x ^{2} – 6 x + 8 =
5. x ^{2} – 11 x – 12 =
6. x ^{2} – 9 x + 14 =
7. x ^{2} + 7 x + 10 =
8. x ^{2} + 4 x – 21 =
9. x ^{2} + 13 x + 36 =
10. x ^{2} + 5 x – 24 =
Solutions
1. x ^{2} – 5 x – 6 = ( x – 6)( x + 1)
2. x ^{2} + 2 x + 1 = ( x + 1)( x + 1) = ( x + 1) ^{2}
3. x ^{2} + 3 x – 10 = ( x + 5)( x – 2)
4. x ^{2} – 6 x + 8 = ( x – 4)( x – 2)
5. x ^{2} – 11 x – 12 = ( x – 12)( x + 1)
6. x ^{2} – 9 x + 14 = ( x – 7)( x – 2)
7. x ^{2} + 7 x + 10 = ( x + 5)( x + 2)
8. x ^{2} + 4 x – 21 = ( x + 7)( x – 3)
9. x ^{2} + 13 x + 36 = ( x + 4)( x + 9)
10. x ^{2} + 5 x – 24 = ( x + 8)( x – 3)
Set 3: Factoring Shortcuts When x^{2}is the First Term  Shortcut 1
To review the factoring shortcut when the first term is x ^{2}, go to Factoring Quadratic Polynomials Help.
Practice
1. x ^{2} – 6 x + 9 =
2. x ^{2} – x – 12 =
3. x ^{2} + 9 x – 22 =
4. x ^{2} + x – 20 =
5. x ^{2} + 13 x + 36 =
6. x ^{2} – 19 x + 34 =
7. x ^{2} – 18 x + 17 =
8. x ^{2} + 24 x – 25 =
9. x ^{2} – 14 x + 48 =
10. x ^{2} + 16 x + 64 =
11. x ^{2} – 49 =
( Hint : x ^{2} – 49 = x ^{2} + 0 x – 49)
Solutions
1. x ^{2} – 6 x + 9 = ( x – 3)( x – 3) = ( x – 3) ^{2}
2. x ^{2} – x – 12 = ( x – 4)( x + 3)
3. x ^{2} + 9 x – 22 = ( x + 11)( x – 2)
4. x ^{2} + x – 20 = ( x + 5)( x – 4)
5. x ^{2} + 13 x + 36 = ( x + 4)( x + 9)
6. x ^{2} – 19 x + 34 = ( x – 2)( x – 17)
7. x ^{2} – 18 x + 17 = ( x – 1)( x – 17)
8. x ^{2} + 24 x – 25 = ( x + 25)( x – 1)
9. x ^{2} – 14 x + 48 = ( x – 6)( x – 8)
10. x ^{2} + 16 x + 64 = ( x + 8)( x + 8) = ( x + 8) ^{2}
11. x ^{2} – 49 = ( x – 7)( x + 7)

1
 2
Ask a Question
Have questions about this article or topic? AskPopular Articles
 Kindergarten Sight Words List
 First Grade Sight Words List
 10 Fun Activities for Children with Autism
 Grammar Lesson: Complete and Simple Predicates
 Definitions of Social Studies
 Child Development Theories
 Signs Your Child Might Have Asperger's Syndrome
 How to Practice Preschool Letter and Name Writing
 Social Cognitive Theory
 Theories of Learning